Sistem Penunjang Keputusan Dalam Pemilihan Pegawai Penerima Promosi Jabatan Menggunakan Metode Simple Additive Weighting dan Weighted Product - Gultom, Herwis; Isnanto, Muhamad Hari (Forum Kerjasama Pendidikan Tinggi (FKPT), 2024)
Human resources are productive individuals who work as drivers of an organization needed for operational activities in it. PT. Citra Baru Perkasa is a private company that manages human resources, so it is not uncommon for problems to occur in its management, in this case to assess employees who receive promotions at PT. Citra Baru Perkasa which is carried out every 1 year, there are several problems that occur in the process of assessing and selecting employees receiving promotions, namely when the assessment process of promoted employees carried out by managers still uses questionnaire paper and in the process of calculating the assessment is only determined from the average value on each criterion, this makes the calculation look inaccurate and less accurate. Based on the existing problems, a solution was obtained by building a decision support system using two methods, namely Simple Additive Weighting (SAW) and Weighted Product (WP), The purpose of building this system is to help reduce errors and simplify the assessment process. The results of this study showed that one of the employees of PT. Citra Baru Perkasa is eligible for promotion. This is based on the calculation results using both methods, namely an employee named Kurniasari who has a value of 1 using the SAW method and 0.210 with the WP method.